Abortion policies at the bedside: incorporating an ethical framework in the analysis and development of abortion legislation - Hersey, Alicia E. (Journal of medical ethics, 2024)
About 6% of women in the world live in countries that ban all abortions, and 34% in countries that only allow abortion to preserve maternal life or health. In the USA, over the last decades—even before Dobbs v. Jackson Women’s Health Organization overturned the federal right to abortion—various states have sought to restrict abortion access. Often times, this legislation has been advanced based on legislators’ personal moral values. At the bedside, in contrast, provision of abortion care should adhere to the normative principles of medical ethics and reproductive justice, centreing patients and their individual reproductive intentions and desires. Abortion regulations, through their influence on patients and providers, may facilitate or impede such ethical care at the bedside. In this paper, we present a framework to model how abortion legislation should fit into the patient-provider relationship and to clarify the dynamics by which legislation may affect healthcare encounters. Our proposed framework serves as a tool to analyse the ethical impact of abortion regulations. We propose a model for assessing abortion policies based not on legislators’ or advocates’ individual moral claims, but on the shared, normative framework of clinical medical ethics. Through contrasting case studies, we demonstrate how a robust normative ethical framework can recentre patients and their reproductive needs. Our model is one way to account for—and safeguard—patients’ diverse viewpoints and needs in the development of abortion policy, and it can serve to ground narratives for advocacy by healthcare workers and their professional organisations.